Structural optimal design and power generation characteristics of a bionic type nautilus vertical axis wind turbine. Issue 1 (13th October 2021) - Li, Zheng; Gao, Menghai; Cao, Xin; Cheng, Liyuan; Wang, Xueting; An, Guoqing; Sun, Hexu
Abstract: Nautilus vertical axis wind turbine is a new breed which is being designed and developed through bionics and geometry, this kind of wind turbine is not only novel in appearance, and stable in structure, but also has excellent aerodynamic performance. Based on this type of wind turbine, combined with its structural characteristics, this paper designed 20 prototypes by continuously adjusting the structural parameters of the spiral blades. The performance of these prototypes is compared by simulation, the optimal structure of this kind of wind turbine is selected. This optimized wind turbine has a strong ability to collect wind energy and can obtain higher wind energy utilization in a wider range of wind speed, the maximum wind energy utilization rate reaches 32.842%. Then the wake characteristics are analysed, the reasonable arrangement is designed. This paper also built an equal scale reduced version of the real object using a 3D printer, and assembles it with a small disc type electric machine to construct a vertical axis wind power generation apparatus. Finally, experiments are conducted in a real environment to analyse the rotational speed and voltage waveform of this apparatus under different operating conditions experimentally.